Transenteric delivery of antibodies via an orally ingestible robotic pill yields high bioavailability comparable to parenteral administration in awake canines - Yamaguchi, Alyson; Van Dam, Jacques; Dhalla, Arvinder K.; Horlen, Kyle; Imran, Mir; Vo, April T.; Hashim, Mir A. (Frontiers in Drug Delivery, 2022)
Biotherapeutics such as peptides and antibodies are highly efficacious clinically but, unlike conventional medications, cannot be administered orally as they get digested and inactivated. Thus, biotherapeutics require parenteral routes for delivery, such as intravenous, intramuscular or subcutaneous administration. However, these delivery methods have limitations such as poor patient compliance or may require clinical supervision compared to oral therapies. We explored whether a novel, orally administered transenteric delivery system (Robotic Pill) could provide equivalent bioavailability to parenterally administered drugs. Utilizing an awake canine model, we demonstrated that orally administered Robotic Pills containing either human IgG or an anti-cytokine monoclonal antibody directed against either TNFα or interleukin-17A yielded bioavailability equivalent to parenterally administered controls. The ability to achieve clinically relevant blood levels of biotherapeutics via any orally administered preparation represents an important advance in drug delivery.